2020
DOI: 10.37015/audt.2020.200013
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Ultrasound in the Diagnosis and Treatment of Reninoma

Abstract: To investigate the clinical value of ultrasound in the diagnosis and treatment of reninoma. Methods:We retrospectively analyzed the ultrasound findings of 9 patients with reninoma confirmed by pathology after surgical resection in our hospital between September 2012 and August 2019. All patients underwent conventional preoperative ultrasonography. Three underwent contrast-enhanced ultrasound (CEUS) and 3 with complete endogenetic tumor underwent intraoperative ultrasonography.Results: Of the 9 patients with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…They were complete endophytic, and showed hypoenhancement, slow wash in and slow wash out. One was 1.0 × 1.0 × 0.7 cm, the other was 3.0 × 2.0 × 1.0 cm [25]. The small sample size precluded a firm recommendation of contrast enhanced ultrasound for JGCT diagnosis.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…They were complete endophytic, and showed hypoenhancement, slow wash in and slow wash out. One was 1.0 × 1.0 × 0.7 cm, the other was 3.0 × 2.0 × 1.0 cm [25]. The small sample size precluded a firm recommendation of contrast enhanced ultrasound for JGCT diagnosis.…”
Section: Discussionmentioning
confidence: 92%
“…Taken together, contrast enhanced CT should be considered in all cases of JGCT. Contrast enhanced ultrasound might be helpful [4,25]. Li et al reported two cases of JGCT, invisible by previous conventional ultrasound, found by contrast enhanced ultrasound.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation